CHI Conference on Human Factors in Computing Systems Extended Abstracts 2022
DOI: 10.1145/3491101.3519696
|View full text |Cite
|
Sign up to set email alerts
|

“Reality Anchors”: Bringing Cues from Reality into VR on Public Transport to Alleviate Safety and Comfort Concerns

Abstract: Virtual Reality (VR) headsets have the unique capability to create private virtual content anywhere around the user, going beyond the capacities of traditional devices, but are not widely used while travelling, due to safety and comfort concerns. Showing objects from reality -"Reality Anchors" -could help reduce these concerns. We present a user study (N=20) that investigates how the use of real-world cues and different VR environments affect users' feelings of safety, social acceptability, awareness, presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The survey also found that respondents are concerned about unwanted interaction with others and being judged by the passengers sitting around them (Bajorunaite et al 2021). In this line of thought, incorporating actual passengers into a virtual environment through avatars results in decreased security concerns and higher social acceptance (Bajorunaite et al 2022). Therefore, the lack of situational awareness is one of the main problems for the public use of VR application (Williamson et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The survey also found that respondents are concerned about unwanted interaction with others and being judged by the passengers sitting around them (Bajorunaite et al 2021). In this line of thought, incorporating actual passengers into a virtual environment through avatars results in decreased security concerns and higher social acceptance (Bajorunaite et al 2022). Therefore, the lack of situational awareness is one of the main problems for the public use of VR application (Williamson et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The use of Virtual and Augmented Reality (collectively XR) in transport settings, such as autonomous vehicles [17,46,51], trains/buses [4,5,49] and aeroplanes [2,36,45,60] is becoming an area of research and industrial focus. Early vehicular VR research instrumented cars with orientation, velocity and location sensors and used the data to drive immersive game [16] or media [29] experiences that followed the motion of the car.…”
Section: Vr On Passenger Transportmentioning
confidence: 99%
“…Based on these principles, researchers have developed several applications, including driver interfaces [8,12], rear-seat productivity [23], mindfulness experiences [40], AR games [56] and motion sickness mitigations [24,29], a key challenge in vehicular XR [30]. More recently, research and industry has broadened the use of VR to planes [2,36,45,60], trains [5,49] and buses [4]. However, travel spaces are very different from traditional XR interaction spaces in homes and offices, and research is only beginning to explore how XR experiences should be designed to suit the physical and social constraints of transport seating.…”
Section: Vr On Passenger Transportmentioning
confidence: 99%